Visualisasi Trauma Psikologis melalui Representasi Yōkai dalam Anime Mononoke (2007) - Devianti, Anindita Lilie; Pujo Purnomo, Antonius Rahmat (KIRYOKU, 2025)
This study aims to analyze the representation of yōkai in the anime Mononoke (2007) as a visual manifestation of the characters’ psychological trauma. Unlike the portrayal of yōkai in traditional Japanese folklore—which tends to emphasize mythological or horror aspects—Mononoke reconstructs these figures as embodiments of unexpressed inner wounds such as guilt, repression, anger, and loss. This research employs a qualitative-descriptive approach with symbolic and narrative analysis methods, grounded in trauma theory as proposed by Cathy Caruth. The analysis reveals that yōkai in this anime function not merely as horror elements, but as media through which complex psychological conflicts are conveyed. Through symbolism, visual atmosphere, and metaphorical narrative structure, Mononoke gives voice to trauma that cannot be articulated directly. As such, the anime does not simply depict supernatural beings but serves as a reflective space that connects folklore, psychology, and visual cultural expression. This study is expected to contribute to interdisciplinary understanding across Japanese cultural studies, literary psychology, and contemporary media analysis.